Removal Natural Organic Matter (NOM) in Peat Water from Wetland Area by Coagulation-Ultrafiltration Hybrid Process with Pretreatment Two-Stage Coagulation - Mahmud Mahmud; Chairul Abdi; Badaruddin Mu'min (Journal of Wetlands Environmental Management, 2013)
The primary problem encountered in the application of membrane technology was membrane fouling. During this time, hybrid process by coagulation-ultrafiltration in drinking water treatment that has been conducted by some research, using by one-stage coagulation. The goal of this research was to investigate the effect of two-stage coagulation as a pretreatment towards performance of the coagulation-ultrafiltration hybrid process for removal NOM in the peat water. Coagulation process, either with the one-stage or two-stage coagulation was very good in removing charge hydrophilic fraction, i.e. more than 98%. NOM fractions of the peat water, from the most easily removed by the two-stage coagulation and one-stage coagulation process was charged hydrophilic>strongly hydrophobic>weakly hydrophobic>neutral hydrophilic. The two-stage coagulation process could removed UV254 and colors with a little better than the one-stage coagulation at the optimum coagulant dose. Neutral hydrophilic fraction of peat water NOM was the most influential fraction of UF membrane fouling. The two-stage coagulation process better in removing the neutral hidrophilic fraction, while removing of the charged hydrophilic, strongly hydrophobic and weakly hydrophobic similar to the one-stage coagulation. Hybrid process by pretreatment with two-stage coagulation, beside can increased removal efficiency of UV254 and color, also can reduced fouling rate of the ultrafiltration membraneIt must not exceed 250 words, contains a brief summary of the text, covering the whole manuscript without being too elaborate on every section. Avoid any abbreviation, unless it is a common knowledge or has been previously stated.